(untitled) (Philological Studies, 2019)
: The Macedonian Kingdom had very many capable rulers who provided free politic, economic, military and cultural development of the state towards the pedestal of the powerful Balkans factor and the world empire through decades. Among them special place takes the Macedonian king Archelaus I (413–399 B.C.) who successfully stroke back at the Hellenic world on all fields of the social, politic, economic and cultural life. In rivalry for prestige he used all the traditional Macedonian experience but without reserve he accepted, supported and propagandized the prohellenism not to assimilate his people but to give new civilization glow and reputation to the king court and with the prohellenic propaganda to acquire the Hellenic world in order to impose more easily the Macedonian political hegemony. After he ensured the throne, for quick development of the state in order to keep pace with the contemporary civilization course he performed important politic, economic, military and cultural reforms.